IMPROVING STORY WRITING SKILLS WITH MIND MAPPING ASSISTED BY VIDEO AND PICTURE MEDIA TO CLASS V STUDENTS AT SDN KAMOJING KARAWANG DISTRICT - Moch Irfan Hikamudin; Tatat Hartati (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
The pur pose of this study was to obtain empirical data related to story writing skills for fifth-grade students at SDN Kamojing by using Mind Mapping assisted by video and picture media. Ideally, the teacher is able to apply the right learning methods and media in learning to write story essays, so that the learning can be memorable for students. The subject s of this st udy were the fifth-grade students of SDN Kamojing in Cikampek Subdistrict, Karawang District in the 2018/2019 school year, totaling 34 students. The research method used is Classroom Act ion Research. T his research was carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection.The method of data collection is done through tests, observing student learning activities and teacher performance when learning takes place.The indicator of the success in this study is the average value of student learning outcomes 70, with a minimum percentage of completeness of 85%. Seen from the evaluation of the first cycle and second cycle, the results obtained from the average grade increased from the pre-test which was only 64.88 with 26.47% learning completeness to 69.88 with 44.12% completeness in the first cycle. These results continued to increase when the second cycle was carried out with an average value of 80.17 with 88.23% learning completeness. Based on the results obtained, it can be concluded that the Mind Mapping assisted by video and picture media can improve students' story writing skills in Indonesian language learning. The use of Mind Mapping can make it easier for students to express their ideas in the form of stories and make students more creative, active and motivated in learning to write stories.